2018
DOI: 10.1007/s10569-018-9865-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical lifetime survey of geostationary transfer orbits

Abstract: In this paper, we study the long-term dynamical evolution of highly-elliptical orbits (HEOs) in the medium-Earth orbit (MEO) region around the Earth. The real population consists primarily of Geosynchronous Transfer Orbits (GTOs), launched at specific inclinations, Molniya-type satellites and related debris. We performed a suite of long-term numerical integrations (up to 200 years) within a realistic dynamical model, aimed primarily at recording the dynamical lifetime of such orbits (defined as the time needed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The top diagrams show the population for e = [0 : 0.9] and i = [0 : 90 • ], while the bottom diagrams focus around the GNSS groups. We refer the reader to Skoulidou et al (2018) for a recent more detailed study of the long-term dynamics of the GTO and Molniya populations.…”
Section: Medium Earth Orbit Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The top diagrams show the population for e = [0 : 0.9] and i = [0 : 90 • ], while the bottom diagrams focus around the GNSS groups. We refer the reader to Skoulidou et al (2018) for a recent more detailed study of the long-term dynamics of the GTO and Molniya populations.…”
Section: Medium Earth Orbit Environmentmentioning
confidence: 99%
“…Of course, atmospheric drag is relevant for GTO and Molniya evolution, as expounded on inSkoulidou et al (2018).6 Note that the satellite's initial node and perigee angles were taken relative to the equatorial lunar values at the corresponding epoch.…”
mentioning
confidence: 99%
“…The nonnegligible collision risks posed by these LEO-GEO transiting spacecraft has motivated both theoretical study and practical implementation (Armellin et al, 2015;Colombo et al, 2015;Merz et al, 2015). Even for the, seemingly more simple, inclined, nearly circular orbits of the navigation satellites, no official guidelines exist, and recent analyses have shown that the problem is far too complex to allow of an adoption of the basic geosynchronous graveyard strategy (Rosengren et al, 2015;Daquin et al, 2016;Celletti et al, 2016;Gkolias et al, 2016;Rosengren et al, 2017;Skoulidou et al, 2017) Fig. 1.…”
Section: The Cataloged Space Debrismentioning
confidence: 99%
“…However, we consider here a relatively coarse grid of initial conditions, spanning the complete LEO to GEO distributions in the whole range of e and i. The higher-resolution exploration, using grids specifically tailored to each orbital region based on the spatial densities of operational orbits, is presented elsewhere (Skoulidou et al, 2017;Gkolias and Colombo, 2017;Alessi et al, 2018a) or is forthcoming (Alessi et al, 2018b;Skoulidou et al, submitted for publication). Note, however, that our coarse grid also covers large parts of near-Earth space (particularly in the MEO region) that are currently not used much in operations and are typically excluded from similar studies.…”
Section: Grid Definition For Numerical Studymentioning
confidence: 99%
“…Examples of the maps obtained, for the different orbital regimes are shown in Figures 2-5. All the maps produced can be found in the website of the project (http:\redshift-h2020.eu) and the theoretical analysis of the results obtained in the mapping can be found in [2][3][4][5][6] and cannot be repeated here for lack of space. Similarly, Figure 3 shows the same map but with only the satellites now highlighted with red circles.…”
Section: Dynamical Mappingmentioning
confidence: 99%